Hubungan Pacar terhadap Perilaku Seks Pranikah pada Remaja di SMP Negeri 16 Kecamatan Sukajadi Pekanbaru - Qomariah, Siti (KESMARS: Jurnal Kesehatan Masyarakat, Manajemen dan Administrasi Rumah Sakit, 2018)
Teens sexual behavior in dating is a manifestation of a sex drive from glancing the sensual part of couples to intercourse performed by teenagers. Sexual activity seems to have become a common thing done by adolescent dating. The purpose of this study to determine the relationship of girl or boy friends to sexual behavior in adolescents at SMP Negeri 16 Sukajadi kecamatan Pekanbaru. The research used is quantitative analytic observational (cross sectional) with elements of independent and dependent variables. The population in this study is all students of class VII SMPN 16 Sukajadi District Pekanbaru. The sample is all students of class VII SMPN 16 Sukajadi District Pekanbaru. With a sample size of 186 respondents. Sampling was done in total sampling. The data used is the primary data by spreading the questionnaire. The data were analyzed by univariate, bivariate with chi-square test. The result of bivariate analysis got the result of p-value (0,000) lees than a = 0,05, that is there is relationship of girlfriend with premarital sex behavior in adolescent. The conclusion in this study is there is a relationship of girlfriend to pre-marital sex behavior in adolescents at SMP Negeri 16 Kec. Sukajadi Pekanbaru. Keywords: Behavior, Adolescent, Premarital Sex